2019
DOI: 10.1016/j.ajo.2019.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Characteristics and Risk Factors of Myopic Maculopathy in an Older High Myopia Population—Based on the New Classification System (ATN)

Abstract: PURPOSE: To investigate the characteristics, mergers, and risk factors of different types of myopic maculopathy (MM) in a highly myopic population. DESIGN: Population-based, cross-sectional study. METHODS: A total of 1086 eyes (762 patients) were enrolled. Each participant underwent detailed ocular examinations. Combining the fundus photographs and optical coherence tomography images, types of MM were assessed as myopic atrophy maculopathy (MAM), myopic tractional maculopathy (MTM), or myopic neovascular macul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 37 publications
5
43
1
Order By: Relevance
“…The presence of this elevated tissue within the LMH rendered the floor thicker and may prevent a full-thickness floor defect. One recent study involving maculopathy in high myopia reported that thinner macular choroidal thickness may be associated with myopic atrophic and neovascular maculopathy, but not with MTM [11]. The present data further showed that the baseline subfoveal choroidal thickness failed to predict the development of FD or FTMH.…”
Section: Plos Onecontrasting
confidence: 49%
See 1 more Smart Citation
“…The presence of this elevated tissue within the LMH rendered the floor thicker and may prevent a full-thickness floor defect. One recent study involving maculopathy in high myopia reported that thinner macular choroidal thickness may be associated with myopic atrophic and neovascular maculopathy, but not with MTM [11]. The present data further showed that the baseline subfoveal choroidal thickness failed to predict the development of FD or FTMH.…”
Section: Plos Onecontrasting
confidence: 49%
“…Based on the new grading system [11], the severity of myopic atrophic maculopathy was classified as follows: A0, no myopic retinal lesions; A1, tessellated fundus; A2, diffuse PLOS ONE chorioretinal atrophy; A3, patchy chorioretinal atrophy; and A4, macular atrophy. Eyes with A2 or higher-grade retinal lesions were considered to have myopic atrophic maculopathy.…”
Section: Clinical Characteristics and Oct Parametersmentioning
confidence: 99%
“…And the research of posterior fundus changes in PM also found that LCs often appeared at the early stage of MM, and the young individuals often do not have noticeable staphyloma or early atrophic changes of the retina [20]. However, the ATN system classi ed LCs into the neovascular group, which may lead to the classi cation of someLCs that may develop into patchy atrophy as the neovascular lesion and further impact the validity of this classi cation system in a long-term progress observation [21]. Consequently, further study to determine the standard of LCs identi cation and modi cation of LCs classi cation was necessary and important.…”
Section: Discussionmentioning
confidence: 99%
“…When fundus occurred macular hemorrhage, the T lesion may be affected and frequently misdiagnosed as foveal detachment (T3), and the macular holes with retinal detachment (T5) lesion often affected the fundus photographs quality that leads to grade A stage was di cult to identi ed. Chen and colleagues [21] in the research of the morphological characteristics and risk factors of MM proposed that the coexistence of the three components could in uence the correlation between risk factors and speci c type of MM. Therefore, dissolving the impact of coexistence among the three components, whether in accurative diagnosis or observation of the progression of MM was still a challenge.…”
Section: Discussionmentioning
confidence: 99%
“…The choroid is sometimes up to 10 times thinner that in an emmetropic eye [7]. Choroid thickness is a direct risk factor both for developing myopic retinal changes and for developing glaucoma [8,9]. Central and peripheral retinal degeneration in particular contributes to an increased rate of visual impairment and blindness with high myopia [10].…”
Section: Introductionmentioning
confidence: 99%